Direction of Relationship between NASDAQ Stock Return and Inflation - Surana, Vibha (2007)
A considerable literature exists that examines the relationship between stock market returns and a range of macroeconomic and financial variables over a number of different stock markets and time horizons. Chen, Roll and Ross (1986) have argued that stock returns should be affected by any factor that influences future cash flows or the discount rate of those cash flows.